Tinjuan Kembali Seni Cadas di Maluku - Marlon NR Ririmasse (Kapata Arkeologi, 2007)
Rock Art sites in Mollucas is a part of Rock Art Bridge over Mainland Asia, South East Asia Archipelago, to Australia and Oceania. Although the existence of the rock art in this region suprisingly has been researched since a century ago, seems like there is not enough attention has been given to this kind of sites neither research or preservation . This article tries to refer back to the rock art research histories in Mollucas in order to explore the prospects of its studies in the future and how we can manage this valuable heritage.